Public's perspectives on guideline‐recommended self‐medication consultations in German community pharmacies. (18th July 2020) - Seiberth, Jasmin Mina; Moritz, Katharina; Vogel, Carl Friedrich; Bertsche, Thilo; Schiek, Susanne
Abstract: The aim of this study was to assess the public's opinions and expectations of self‐medication consultations in German community pharmacies with special emphasis on the acceptance of guideline‐recommended consultation. In a cross‐sectional study in the city centre of Leipzig, Germany, we conducted a questionnaire‐based survey administered via an interview with passers‐by from June to September 2018. The structured questionnaire contained questions assessing (I) previous experience with self‐medication consultations, (II) possible reasons for declining self‐medication consultations, (III) the attitude towards information gathering and (IV) expectations of self‐medication consultations. (I) 92% of the 963 respondents stated they were generally satisfied with self‐medication consultations in community pharmacies. Around one‐fifth of all respondents claimed that they would like to be asked more health‐related questions (22%) and receive more information on non‐prescription drugs (20%). (II) Privacy issues (39%) and reluctance to talk about some medical conditions (43%) were the most frequent reasons for declining self‐medication consultation. (III) Respondents understood the need for answering guideline‐recommended questions (85–96%) and did not mind being asked these questions (70–96%). (IV) Most of the respondents expected to be counselled even if they did not ask for it directly (69%). Pharmacies were further expected to recommend the best drug, even if it was not what the customer initially intended to buy (87%). However, more than half of the respondents would consider counselling as unimportant if they knew exactly which medication they wanted to buy (56%) or if they had used the non‐prescription drug before (70%). The majority also expected to receive guideline‐recommended drug information (each item at least 52%). Thus, our study shows that respondents were mostly in line with the required standards of self‐medication counselling guidelines. Customers expect high‐quality counselling on self‐medication. These findings support pharmaceutical staff's understanding of customers' barriers and expectations during self‐medication consultations.